Analysis of Blood Donor Health Examination Results based on Body Mass Index Value with Increased Blood Pressure - Firanti, Firanti; Riawati , Danik (CV. Science Tech Group, 2025)
Health checks determine a person's health condition; for example, when going to donate blood, general selection checks are carried out such as height, weight, blood pressure, hemoglobin levels, and so on. This research aims to analyze the relationship between a person's nutritional status category and blood pressure results. This research is an analytical observational study with a cross-sectional design. The population consisted of all blood donors who were present at the UDD PMI Cirebon Regency building, totaling 260 respondents, using an accidental sampling technique who happened to come to donate blood. The sample size was determined by referring to Isac and Michael's table, which resulted in 149 respondents with an error rate of 5%. The data collected is in the form of secondary and primary data. The data analysis used is univariate analysis in the form of a frequency distribution table and bivariate analysis using the partial correlation test.